Treatment strategies and prognostic factors in secondary central nervous system lymphoma: a multicenter study of 124 patients - Treiber, Hannes; Nilius-Eliliwi, Verena; Seifert, Nicole; Vangala, Deepak; Wang, Meng; Seidel, Sabine; Mika, Thomas; Marschner, Dominik; Zeremski, Vanja; Wurm-Kuczera, Rebecca; Caillé, Léandra; Chapuy, Claudia I.; et al. (HemaSphere, 2023)
Secondary central nervous system lymphoma (SCNSL) is a rare and difficult to treat type of Non-Hodgkin lymphoma characterized by systemic and central nervous system (CNS) disease manifestations. In this study, 124 patients with SCNSL intensively treated and with clinical long-term follow-up were included. Initial histopathology, as divided in low-grade, other aggressive, and diffuse large B-cell lymphoma (DLBCL), was of prognostic significance. Overall response to induction treatment was a prognostic factor with early responding DLBCL-SCNSL in comparison to those non-responding experiencing a significantly better progression-free survival (PFS) and overall survival (OS). However, the type of induction regime was not prognostic for survival. Following consolidating high-dose chemotherapy and autologous stem cell transplantation (HDT-ASCT), DLBCL-SCNSL patients had better median PFS and OS. The important role of HDT-ASCT was further highlighted by favorable responses and survival of patients not responding to induction therapy and by excellent results in patients with de novo DLBCL-SCNSL (65% long-term survival). SCNSL identified as a progression of disease within 6 months of initial systemic lymphoma presentation represented a previously not appreciated subgroup with particularly dismal outcome. This temporal stratification model of SCNSL diagnosis revealed CNS progression of disease within 6 months as a promising candidate prognosticator for future studies.
Gesehen am 29.08.2023